THE EFFECT OF SOAKING, WASHING AND FRYING ON THE CONCENTRATION OF FORMALDEHYDE IN SANGE BELAH SALTY FISH - Jutti Levita -; Wiwiek Indriyati -; Resmi Mustarichie - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2010)
Formaldehyde in food has developed as public issue in the last two years. Several foods, such as salty fish, wet noodles and tofu were laboratorically proven using formaldehyde as preservative. A study on the effect of soaking and frying towards the concentration of formaldehyde in salty fish has been carried out. Sange belah was chosen as the model. The fish was soaked in formaldehyde solution (250 ppm in concentration) for 12 hours then it was washed, fried, and distilled in closed system. Distillate was reacted with Nash Reagent. The yellow color formed was measured spectrophotometrically at λ 415 nm. Result showed that there was a decreasing of formaldehyde concentration in the sample (Δ 63.27% after washing and Δ 83.03% after frying).Keywords: Formaldehyde, salty fish, sange belah